Corporate social responsibility in Egypt: Towards creating shared value - Hegazy, Alya (AUC Knowledge Fountain, 2018)
This study assesses if the practice of corporate social responsibility (CSR) in Egypt has moved beyond the understanding of charity and towards a model of creating shared value (CSV). This study is an important contribution given the growing interest in CSR in Egypt and the limited contextualized research on the topic. The conceptual framework used to guide this research is based on the "Creating Shared Value" model developed by Porter and Kramer. The research methodology is built on semi-structured in depth interviews with thirteen leading CSR practitioners and experts in Egypt. The study findings revealed valuable insights on the current understanding and practice of CSR and CSV in Egypt. Study results highlight that the understanding of CSR has evolved, at least amongst most of the study sample, from the traditional perception linked to charity, donation and societal obligation into a more comprehensive construction that promotes greater integration of a company's responsibility towards their workforce, society and environment and incorporation of sustainability principles and models. More specifically, the idea of creating shared value is in fact gaining prominence within the private sector in Egypt. There are, however, still elements of the traditional model of CSR to be found as evidenced through the volunteering and donation-based activities as well as the philanthropic programs. Interestingly enough, philanthropy is taking a more strategic, developmental and sustainable approach compared to before. This study also provides a great deal of insight on the challenges faced in the practice of CSR and offers some suggestions and policy recommendations to help advance the CSR and CSV understanding and practice in Egypt.